BIODEGRADACION FUNGICA DE POLIURETANO RÍGIDO - Araceli Loredo; Andres Argüello; Raul Rodríguez-Herrera; Gerardo Gutiérrez-Sánchez; Alondra Escamilla; Cristóbal Aguilar (Química Nova)
Polyurethane (PU) is one of the most widely used polymer materials. This generates a serious environmental problem because of its poor biodegradability since most of the native microorganisms cannot use it as a source of nutrients. Several techniques involving mechanical and chemical processes have been used for its recovery and reuse; however, the problem of contamination has not been solved, and recently research has focused on developing strategies that use different microorganisms for the biodegradation of PU. In this work, the biodegradation and enzymatic capacity of three fungal strains were evaluated. Thermogravimetric and infrared spectrophotometry analyzes were used to evaluate the ability of the three fungal strains to biodegrade PU and also their enzymatic activities were studied. It was found that a strain of Trichoderma was able to modify the PU structure enough that the changes were detected by both TGA and FTIR. These changes can be caused by urease activity that breaks down carbon-nitrogen bonds in the structure because the signals suggesting the formation of carboxylic acids and decreasing corresponding to carbon-nitrogen bonds of the urethane bond are increased.